(untitled) (Fiep Bulletin - online, 2011)
The present article looked recounts it of the sport adapted from his appearance to the current times, demonstrating his international evolution and nationally. The sport adapted from their first reports, it is bringing a new perspective for the people with deficiency. The sport adapted in Brazil appeared to contemplate our people with deficiency and this way the club of the paraplegic ones was founded, where people with several deficiencies were assisted aiming at the rehabilitation of them through the sport. One of the disseminated sports is the basketball on wheels, in the which is a paraolimpic modality, and in Brazil such modality it is very spread and the tournaments are distributed in all of the states. In Presidente Prudente, the adapted sport appeared at the clinic of physical rehabilitation in the campus of the From São Paulo State University with the intention of using the sport as source reabilitadora and social to have harmed medulares visitors of her, in 1998 the adapted sport it appears in this city in the project AMA Project Adapted Motive Activity, as first modality of this, the basketball on wheels, in 2005 the project won magnitude and the athletics was inserted adapted in their several proofs, of this participating in the events of the Comitê Paraolimpico Brasileiro. In late 2007, with the increasing demand of the project was founded on 03 December, the Adapted Sports Association of Presidente Prudente, a non-profit that aims to cover the athletes giving support to participate in national competitions and their respective international procedures